PELATIHAN APLIKASI MICROSOFT EXCEL PEMBUATAN SLIP UPAH KARYAWAN PADA UMKM PENGRAJIN TAHU RUMAHAN KECAMATAN CIMANGGIS DEPOK - Putri, Sukma; Rahmadani; Kurniawan, Ahmad (Jurnal Abdi Citra, 2024)
Small, Micro and Medium Enterprises are one of the backbones of the community economy in the Cimanggis sub-district, Depok. One of the known products is tofu which is produced by MSME business actors in the Cimanggis sub-district, Depok. MSME bag craftsmen in the region still use simple systems and technology in running their business including production, administration,marketing, financial recording and payroll. The aim of this service activity is to provide and introduce how to make salary slips to help prepare and transparency salaries/wages for employees in these MSMEs. The service was carried out online using Zoom Meeting media in the form of presentations and practice (tutorials) in making pay slips, presentations using the Microsoft Office Powerpoint and Microsoft Office Excel applications. Participants in service activities are representatives of MSME business actors in Cimanggis sub-district, Depok and fellow Community Service (PKM) participants. The implementation of the service received enthusiasm from the participants because it was in accordance with the conditions of business actors and could be implemented immediately, easily and cheaply.